This preview shows page 1. Sign up to view the full content.
Unformatted text preview: m 6  n , then m 2 6  n 3 , is false. (Hint: Use a counterexample.) Problem 3 . Let a,b,n Z . Prove that if n > 0, then gcd( an,bn ) = n gcd( a,b ). Problem 4 . Let a,b Z . Prove that gcd( a,b ) = gcd(2 a3 b,a2 b ). Problem 5 . Let a,b,c Z . Prove that gcd( ab,c ) = 1 if and only if gcd( a,c ) = gcd( b,c ) = 1. 1...
View
Full
Document
This note was uploaded on 12/18/2010 for the course ECONOMICS 120 taught by Professor Mesta during the Spring '10 term at Wilfred Laurier University .
 Spring '10
 Mesta

Click to edit the document details